Understanding Rwandan Agricultural Households' Strategies to Deal with Prime-Age Illness and Death: A Propensity Score Matching Approach - Donovan, Cynthia; Bailey, Linda A. (International Food Policy Research Institute, 2006)
The increasing prevalence of HIV in Rwanda, along with the likelihood of continued effects of the genocide of 1994, suggests that many rural households may be facing extreme stress, and their agricultural production may be changing. Policymakers and development practitioners seek to understand how Rwandan households are affected and how they are reacting to the stress so that development policies can best support improvements in rural livelihoods under this changing environment. If production systems are shifting to less nutritious crop mixtures or ones that increase the potential for soil erosion on the hillsides, measures may be needed to counterbalance the negative effects.